Generation and screening of a comprehensive Mycobacterium avium subsp. paratuberculosis transposon mutant bank - Rathnaiah, Govardhan; Lamont, Elise A.; Harris, N. Beth; Fenton, Robert J.; Zinniel, Denise K.; Liu, Xiaofei; Sotos, Josh; Feng, Zhengyu; Livneh-Kol, Ayala; Shpigel, Nahum Y.; Czuprynski, Charles J.; Sreevatsan, Srinand; et al. (Frontiers in Cellular and Infection Microbiology, 2014)
Mycobacterium avium subsp. paratuberculosis (MAP) is the etiologic agent of Johne’s Disease in ruminants. This enteritis has significant economic impact and worldwide distribution. Vaccination is one of the most cost effective infectious disease control measures. Unfortunately, current vaccines reduce clinical disease and shedding, but are of limited efficacy and do not provide long-term protective immunity. Several strategies have been followed to mine the MAP genome for virulence determinants that could be applied to vaccine and diagnostic assay development. In this study, a comprehensive mutant bank of 13,536 MAP K-10 Tn5367 mutants (P > 95%) was constructed and screened in vitro for phenotypes related to virulence. This strategy was designated to maximize identification of genes important to MAP pathogenesis without relying on studies of other mycobacterial species that may not translate into similar effects in MAP. This bank was screened for mutants with colony morphology alterations, susceptibility to D-cycloserine, impairment in siderophore production or secretion, reduced cell association, and decreased biofilm and clump formation. Mutants with interesting phenotypes were analyzed by PCR, Southern blotting and DNA sequencing to determine transposon insertion sites. These insertion sites mapped upstream from the MAP1152-MAP1156 cluster, internal to either the Mod operon gene MAP1566 or within the coding sequence of lsr2, and several intergenic regions. Growth curves in broth cultures, invasion assays and kinetics of survival and replication in primary bovine macrophages were also determined. The ability of vectors carrying Tn5370 to generate stable MAP mutants was also investigated.